Analysis for Resolution of Bistatic SAR Configuration with Geosynchronous Transmitter and UAV Receiver - Yicheng Jiang; Zhuoqun Wang (International Journal of Antennas and Propagation)
Bistatical SAR with geosynchronous illuminator and unmanned aerial vehicle receiver (GEO-UAV BiSAR) has significant potential advantages in the field of continuous local observation under a dangerous environment within nearly 24 h. Due to the extreme platform velocity differences, the ellipse orbital movement of GEOSAR makes this BiSAR configuration not like the conventional spaceborne BiSAR. In this paper, based on the orbital kinetic characteristic of GEOSAR, we theoretically analyze the variations of bistatic configuration effect on common azimuth coverage and coherent accumulated time. In addition, two-dimension the resolution is deduced by geometrical configuration on the basis of gradient method. The simulations show that the appropriate selection of initial bistatic configuration can restrain from the appearance of the dead zone in common coverage. And the image results are obtained by frequency domain RD based on Method of Series Reversion (MSR). It is shown that GEO-UAV BiSAR has the high resolution ability.